Social Media Factors and Teen Gadget Addiction Factors in Indonesia - Nesti Anggraini Santoso; Alwiyah; Efa Ayu Nabila (ADI Publisher, 2021)
Social media users in Indonesia are growing rapidly since its emergence. In 2019, one of the largest social media platforms, Facebook has 3 billion users worldwide as well as 130 million users from Indonesia. Moreover, other social media such as Instagram also experienced significant growth with most of its users being teenagers. Massive use of social media is caused by more than 100 million active users using gadgets or smartphones to open apps such as social media. Widespread use of social media and gadgets not only has a positive impact but also negative impacts such as mental and behavioral disorders if the user is already addicted. Therefore, the need to know the factors that influence social media addiction and gadgets in Indonesia is necessary to prevent the occurrence of social media and gadget addiction. In this paper, the influence factors of social media addiction and gadgets in Indonesia are examined using several techniques such as data science, partial least square, and structural equation modeling. Research result: Time, Productivity and Relationships are factors that influence social media addiction and gadgets, whereas Mind is not a factor that affects social media addiction and gadgets.